Effect of yoga on Muscular strength of fencing players (International Journal of Food and Nutritional Sciences, 2023)
Vedas, Upanishads, Puranas, Bhagavad Gita, Patanjali Yoga Sutras, Hatha Pradipika, Gherandasamuga, Shivsamhita, Yogavashishtha, Gorakshpeeth, Hatharatnavali, Yogataravali etc. have contributed a lot in the historical tradition of yoga. Yoga was intended for spiritual development, but is now used for its incidental benefits such as managing stress and lifestyle-related disorders. Yoga practice helped mentally challenged people to improve their mental ability. Some degree of functional ability was restored after practicing yoga in physically handicapped subjects. Yoga is an ancient Indian science and way of life. The practice of yoga has been found to be therapeutically useful in a variety of diseases such as diabetes, hypertension as well as other psychiatric ailments. The practice of yoga can play a role in all sports, both physically and mentally. This research paper has focused on the importance of Yogic scriptures for the fencing players.